Barriers and facilitators to initial and continued attendance at community‐based lifestyle programmes among families of overweight and obese children: a systematic review. (10th November 2016) - Kelleher, E.; Davoren, M. P.; Harrington, J. M.; Shiely, F.; Perry, I. J.; McHugh, S. M.
Summary: The success of childhood weight management programmes relies on family engagement. While attendance offers many benefits including the support to make positive lifestyle changes, the majority of families referred to treatment decline. Moreover, for those who do attend, benefits are often compromised by high programme attrition. This systematic review investigated factors influencing attendance at community‐based lifestyle programmes among families of overweight or obese children. A narrative synthesis approach was used to allow for the inclusion of quantitative, qualitative and mixed‐method study designs. Thirteen studies met the inclusion criteria. Results suggest that parents provided the impetus for programme initiation, and this was driven largely by a concern for their child's psychological health and wellbeing. More often than not, children went along without any real reason or interest in attending. Over the course of the programme, however, children's positive social experiences such as having fun and making friends fostered the desire to continue. The stigma surrounding excess weight and the denial of the issue amongst some parents presented barriers to enrolment and warrant further study. This study provides practical recommendations to guide future policy makers, programme delivery teams and researchers in developing strategies to boost recruitment and minimise attrition.